Risk factors for fatty pancreas and effects of fatty infiltration on pancreatic cancer - Otsuka, Nao; Shimizu, Kyoko; Taniai, Makiko; Tokushige, Katsutoshi (Frontiers in Physiology, 2023)
Objective: This study clarified the risk factors and pathophysiology of pancreatic cancer by examining the factors associated with fatty pancreas. Methods: The degree of fatty pancreas, background factors, and incidence of pancreatic cancer were examined among nonalcoholic fatty liver disease (NAFLD) patients (n = 281) and intraductal papillary mucinous neoplasm (IPMN) patients with a family history of pancreatic cancer (n = 38). The presence of fatty pancreas was confirmed by the pancreatic CT value/splenic CT value ratio (P/S ratio). Immunohistochemical staining was performed on 10 cases with fatty pancreas, confirmed via postoperative pathology. Results: Fatty pancreas occurred in 126 patients (44.8%) in the NAFLD group who were older (P = 0.0002) and more likely to have hypertension (P <0.0001). The IPMN group had 18 patients (47.4%) with fatty pancreas, included more men than women (P = 0.0056), and was more likely to have patients with hypertension (P = 0.0010). On histological examination, a significant infiltration of adipocytes into the acini from the pancreatic interstitium induced atrophy of the pancreatic parenchyma, and both M1 and M2 macrophages were detected in the area where adipocytes invaded the pancreatic parenchyma. Accumulation of p62 and increased positive staining of NQO1 molecules related to autophagy dysfunction were detected in pancreatic acinar cells in the fatty area, acinar-ductal metaplasia, and pancreatic cancer cells. The rate of p62-positive cell area and that of NQO1-positive cell area were significantly higher in the fatty pancreatic region than those in the control lesion (pancreatic region with few adipocyte infiltration). Furthermore, the rate of p62-positive cell area or that of NQO1-positive cell area showed strong positive correlations with the rate of fatty pancreatic lesion. These results suggest that adipocyte invasion into the pancreatic parenthyme induced macrophage infiltration and autophagy substrate p62 accumulation. High levels of NQO1 expression in the fatty area may be dependent on p62 accumulation. Conclusions: Hypertension was a significant risk factor for fatty pancreas in patients with NAFLD and IPMN. In fatty pancreas, fatty infiltration into the pancreatic parenchyme might induce autophagy dysfunction, resulting in activation of antioxidant proteins NQO1. Thus, patients with fatty pancreas require careful follow-up.